Up-regulation of dorsal root ganglia BDNF and trkB receptor in inflammatory pain: an in vivo and in vitro study - Lin, Ya-Tin (BioMed Central, 2011)
BACKGROUND: During inflammation, immune cells accumulate in damaged areas and release pro-inflammatory cytokines and neurotrophins. Brain-derived neurotrophic factor (BDNF) plays a neuromodulatory role in spinal cord dorsal horn via the post-synaptic tyrosine protein kinase B (trkB) receptor to facilitate pain transmission. However, the precise role of BDNF and trkB receptor in the primary sensory neurons of dorsal root ganglia (DRG) during inflammation remains to be clarified. The aim of this study was to investigate whether and how BDNF-trkB signaling in the DRG is involved in the process of inflammatory pain. METHODS: We used complete Freund's adjuvant- (CFA-) induced and tumor necrosis factor-α- (TNF-α-) induced inflammation in rat hindpaw as animal models of inflammatory pain. Quantification of protein and/or mRNA levels of pain mediators was performed in separate lumbar L3-L5 DRGs. The cellular mechanism of TNF-α-induced BDNF and/or trkB receptor expression was examined in primary DRG cultures collected from pooled L1-L6 DRGs. Calcitonin gene-related peptide (CGRP), BDNF and substance P release were also evaluated by enzyme immunoassay. RESULTS: CFA injection into rat hindpaw resulted in mechanical hyperalgesia and significant increases in levels of TNF-α in the inflamed tissues, along with enhancement of BDNF and trkB receptor as well as the pain mediators CGRP and transient receptor potential vanilloid receptor subtype 1 (TRPV1) in DRG. Direct injection of TNF-α into rat hindpaw resulted in similar effects with retrograde transport of TNF-α along the saphenous nerve to DRG during CFA-induced inflammation. Primary DRG cultures chronically treated with TNF-α showed significant enhancement of mRNA and protein levels of BDNF and trkB receptor, BDNF release and trkB-induced phospho-ERK1/2 signal. Moreover, CGRP and substance P release were enhanced in DRG cultures after chronic TNF-α treatment or acute BDNF stimulation. In addition, we found that BDNF up-regulated trkB expression in DRG cultures. CONCLUSIONS: Based on our current experimental results, we conclude that inflammation and TNF-α up-regulate the BDNF-trkB system in DRG. This phenomenon suggests that up-regulation of BDNF in DRG may, in addition to its post-synaptic effect in spinal dorsal horn, act as an autocrine and/or paracrine signal to activate the pre-synaptic trkB receptor and regulate synaptic excitability in pain transmission, thereby contributing to the development of hyperalgesia.